The Determinants of Individual Taxpayer Compliance at KPP Pratama Tarakan - Junaid, Muhammad (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
Based on data from the Performance Report of the Directorate General of Taxes of the Ministry of Finance, up to 2021 shows unsatisfactory results. In addition to fluctuating, taxpayer compliance also never reaches the target that has been set. From this background it is important to further examine the attitude of the tax authorities, tax socialization, and taxpayer knowledge of taxpayer compliance.This study uses a quantitative approach to answer these problems using primary data in the form of a questionnaire. The population in this study are all taxpayers who are registered at KPP Pratama Tarakan. The number of questionnaires distributed in this study were 110 questionnaires distributed within the scope of the Tarakan Primary KPP. However, after going through the questionnaire collection stage, only 100 questionnaires were obtained that could be processed. Before conducting data analysis, the researcher conducted validity and reliability tests on 100 respondents to show how far the questionnaire was reliable and reliable. The data analysis technique used in this research is multiple regression analysis techniqueThe results of testing the hypothesis in this study indicate that the attitude of the tax authorities, tax socialization, and taxpayer knowledge have a positive and significant effect on taxpayer compliance.